The Role of Tourism Awareness Groups (Pokdarwis) in Improving Employee Work Motivation and Community Knowledge as a Strategy for Development of Malang Lon Beach Tourism During the Covid-19 Pandemic (Case Study on Lon Beach Malang Sokobanah Sampang) - Intan Febriyanti; R.M. Mochammad Wispandono (Management Department of Economics and Business Of Trunojoyo Madura University, 2022)
The tourism awareness group is one of the drivers and initiators of development to increase independence and community participation in realizing Lon Malang beach tourism in Sokobanah Sampang as a tourist destination, and is supported by the motivation needed by the community to maintain and preserve in the context of developing Lon Malang Beach. This study aims to find out: (1) To find out the role of Pokdarwis in increasing employee motivation on Lon Malang beach tourism during the Covid-19 pandemic, (2) To find out the strategy for developing Lon Malang beach tourism during the Covid-19 19 pandemic. This study uses a qualitative descriptive method, with 10 informants as resource persons consisting of 1 Pokdarwis chairman, 1 secretary, 1 treasurer, 1 security and order section, 1 tourist attraction section, 1 public relations section, 1 business development section, 1 equipment, 1 local community and 1 visitor/tourist. The sampling technique used is purposive sampling, which is based on certain criteria and considerations. The author obtained data from documents and oral statements from Pokdarwis members, local communities and visiting tourists. The results of this study indicate that: (1) Pokdarwis plays an important role in increasing employee motivation on Lon Malang beach tourism during the Covid-19 pandemic (2) One of the strategies in developing Lon Malang tourism during the Covid-19 pandemic is adding photo spots and interesting games.